Telesna dejavnost prvih šest tednov po porodu - Videmšek, Mateja (Šport (Ljubljana), 2017)
The aim of the article is to present physical activity, and to present tone up and strengthen muscles exercises for mothers during the first six week after the childbirth. Childbirth causes body changes, which it is important, for mothers, to be aware of very soon after childbirth in order to return the body into previous state. Due to a new family member and exhaustion after childbirth, it is difficult for mothers to think about exercise. Since it is very important that pelvic floor muscles and muscles of abdominal wall return to the state before the birth, our article presents exercises that are appropriate during the first six week after the childbirth. Staying in maternity hospital represents a right time for a mother to learn first exercises, which are intended to pelvic floor muscles and the muscles of abdominal wall. Every mother should learn to perform exercises properly, since exercises are performed in a lying position so it does not present a serious effort to the mother.
Keywords: mati; mišice medeničnega dna; mother; pelvic floor muscles; poporodna vadba; postnatal exercises; sport; šport; telesna dejavnost